COVID-19 and the fragmentation of the European interbank market - Melissa Pala (Deutsche Bundesbank, 2024)
This paper provides evidence of a highly fragmented European interbank market that is tightened during the COVID-19 pandemic, when the interbank market was under stress. Using a unique dataset of unsecured, overnight interbank loans at the transactional level allows me to apply advanced panel methods. Furthermore, this paper shows liquidity hoarding during the pandemic and relationship lending as a German phenomenon. In addition, there is evidence that borrowers who have to pay higher rates in the market are more likely to participate in tender auctions and that the COVID-19 pandemic had the greatest impact on smaller interbank borrowers.
Keywords: G01; G15; G18; G21; D85; 330; nterbank Market; Relationship Lending; Liquidity; COVID-19; Monetary Policy